An exploratory study of psychological resilience factors associated with climate change adaptation by subsistence farmers in a rural community in Maruleng, Limpopo Province - Kgopa, Bontle Patience (My University, 2022)
Climate change poses a major threat to both the well-being of people and the environment. Subsistence farmers are particularly affected because they rely on local supply systems that are sensitive to climate variation. The aim of the study was to explore psychological resilience factors associated with climate change adaptation by subsistence farmers in a rural farming community in Maruleng Municipality in Limpopo Province (South Africa). The objectives of the study were to: investigate subsistence farmers' notions of climate change and adaptation; determine the psychological resilience factors influencing the farmers’ adaptation the climate change; determine strategies that the farmers use to cope with climate change; and, based on the farmers’ notions of climate change and adaptation, and the associated resilience factors, develop a psychological explanatory model on climate change adaptation by subsistence farmers. Data were collected through direct interactions with participants using a grounded theory research design. An open-ended interview guide was used to collect data with a sample of 15 participants selected through theoretical sampling within the Maruleng Municipality. The research findings indicate that farmers have limited conceptual knowledge relating to climate change and its causes. The results further indicated that participants have become resilient to climate change through mitigation strategies including mulching, adaptive irrigation techniques and being innovative. From a psychological perspective, the subsistence farmers’ resilience factors that emerged included passion for farming, hope, enthusiasm, courage, acceptance or tolerance, livelihood and a coherent belief system. Based on the findings of the study, a psychological explanatory model in climate change adaptation by subsistence farmers was developed. The explanatory model suggests that resilience factors are influenced by notions and adaptations of climate change. The study is concluded by, among others, recommending that counseling services be made available to farmers to help them deal with the stress associated with the negative impact of climate change.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2022
Keywords: Climate change; Psychological resilience factors; Human adaptation; Adaptation; Subsistence farmers; Maruleng; Adaptability (Psychology); Climatic changes; Subsistence farming; Resilience